Complications of Veress Needle Insertion for Creation of Pneumoperitoneum - Omer Fateh; Muhammad Samir Irfan Wasi (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
Objective: To determine the frequency of  major  and  minor  complications  associated  with  Veress  needle insertion method for creation of pneumoperitoneum  for  laparoscopic  cholecystectomy  procedure. Methods: This is a descriptive study aimed to assess the complications caused by Veress needle in- sertion and to determine the safety profile of this procedure. In this  study  patients  undergoing  laparoscopic cholecystectomy in  Sindh  Government  Qatar  Hospital  were  selected  from  January  2014 to December 2015. Exclusion criteria were established and those patients  having  age  more  than  80 years, procedure converted to open surgery or having previous  history  of  upper  abdominal  surgeries were excluded. Complications occurring during creation of pneumoperitoneum by Veress needle were assessed. Complications were grouped as major and minor  complications.  Major  complications  in-  cluded injury to abdominal viscera and vascular  injuries,  including  injury  to  aorta,  inferior  vena  cava, iliac and mesenteric arteries. Minor injuries included injury to omentum and mesentery. Results: Total of 377 cases of laparoscopic  surgeries  were  included  in  the  study.  In  these  laparoscopic surgeries 3 (0.79%) injuries were  recorded.  All  injuries  recorded  were  categorised  as  minor complications and included two omental injuries and one mesenteric injury.  No  major  complications were recorded including visceral or vascular injuries. Conclusion: It was concluded in this study that Veress needle method for creation of pneumoperitoneum has  good  safety  profile,  being  less  prone  to  major  and  minor  complications,  along  with  being a time-saving procedure.